Minimal Invasive Versus Open Surgery for Colorectal Liver Metastases: A Multicenter German StuDoQ|Liver Registry-Based Cohort Analysis in Germany - Simon Moosburner, MD; Chiara Kettler; Karl H. Hillebrandt, MD; Moritz Blank; Hannes Freitag; Sebastian Knitter, MD; Felix Krenzien, MD; Nora Nevermann, MD; Igor M. Sauer, MD; Dominik P. Modest, MD; Georg Lurje, MD; Robert Öllinger, MD; et al. (Annals of Surgery Open)
Objective:. To compare the outcome of minimally invasive liver surgery (MILS) to open liver surgery (OLS) for resection of colorectal liver metastases (CRLM) on a nationwide level. Background:. Colorectal cancer is the third most common malignancy worldwide. Up to 50% of all patients with colorectal cancer develop CRLM. MILS represents an attractive alternative to OLS for treatment of CRLM. Methods:. Retrospective cohort study using the prospectively recorded German Quality management registry for liver surgery. Propensity-score matching was performed to account for variance in the extent of resection and patient demographics. Results:. In total, 1037 patients underwent liver resection for CRLM from 2019 to 2021. MILS was performed in 31%. Operative time was significantly longer in MILS (234 vs 222 minutes, P = 0.02) compared with OLS. After MILS, median length of hospital stay (LOS) was significantly shorter (7 vs 10 days; P < 0.001). Despite 76% of major resections being OLS, postoperative complications and 90-day morbidity and mortality did not differ. The Pringle maneuver was more frequently used in MILS (48% vs 40%, P = 0.048). After propensity-score matching for age, body mass index, Eastern Cooperative Oncology Group, and extent of resection, LOS remained shorter in the MILS cohort (6 vs 10 days, P < 0.001) and operative time did not differ significantly (P = 0.2). Conclusion:. MILS is not the standard for resection of CRLM in Germany. Drawbacks, such as a longer operative time remain. However, if technically possible, MILS is a reasonable alternative to OLS for resection of CRLM, with comparable postoperative complications, reduced LOS, and equal oncological radicality.